Entanglements of Time, Temperature, Technology, and Place in Ancient DNA Research: The Case of the Denisovan Hominin. (November 2020) - Oikkonen, Venla
The study of ancient DNA (aDNA) has gained increasing attention in science and society as a tool for tracing hominin evolution. While aDNA research overlaps with the history of population genetics, it embodies a specific configuration of technology, temporality, temperature, and place that, this article suggests, cannot be fully unpacked with existing science and technology studies approaches to population genetics. This article explores this configuration through the 2010 discovery of the Denisovan hominin based on aDNA retrieved from a finger bone and tooth in Siberia. The analysis explores how the Denisovan was enacted as a technoscientific object through the cool and even temperatures of Denisova Cave, assumptions about the connection between individual and population, the status of populations as evolutionary entities, and underlying colonialist and imperialist imaginaries of Siberia and Melanesia. The analysis sheds light on how aDNA research is changing the parameters within which evolutionary history is imagined and conceptualized. Through the case study, it also outlines some ways in which the specific technoscientific and cultural entanglements of aDNA can be critically explored.